1914
DOI: 10.1098/rspb.1914.0071
|View full text |Cite
|
Sign up to set email alerts
|

Some accessory factors in plant growth and nutrition

Abstract: Recent research has demonstrated the importance of the presence of minute amounts of certain substances as accessory factors in normal dietaries of man and animals. The most striking examples of the influence of these substances are seen in their curative effect on the diseases of beri-beri and scurvy, and their stimulative effect on the growth of young animals.Beri-beri is caused by the deficiency in a diet of polished rice of a nitrogenous substance, small amounts of which are essential for the metabolism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1945
1945
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Several authors have found evidence of HS improving plant growth and physiology (Bottomley, 1914a(Bottomley, , 1914b(Bottomley, , 1917O'Donnell, 1973;Cacco and Dell'Agnola, 1984;Dell'Agnola and Nardi, 1987;Nardi et al, 1988;Schiavon et al, 2008;Pizzeghello et al, 2013). These positive effects on plants could be ascribed, in the main, to hormone-like activity, as a number of hormones enclosed in the humus structure have been identified (Muscolo et al, 1998;Nardi et al, 2000b;Pizzeghello et al, 2001).…”
Section: Biological Activity Of Humic Substancesmentioning
confidence: 97%
“…Several authors have found evidence of HS improving plant growth and physiology (Bottomley, 1914a(Bottomley, , 1914b(Bottomley, , 1917O'Donnell, 1973;Cacco and Dell'Agnola, 1984;Dell'Agnola and Nardi, 1987;Nardi et al, 1988;Schiavon et al, 2008;Pizzeghello et al, 2013). These positive effects on plants could be ascribed, in the main, to hormone-like activity, as a number of hormones enclosed in the humus structure have been identified (Muscolo et al, 1998;Nardi et al, 2000b;Pizzeghello et al, 2001).…”
Section: Biological Activity Of Humic Substancesmentioning
confidence: 97%
“…Lawes and Gilbert (1905) fi rst demonstrated that soil fertility could be preserved for many years by applying only mineral fertilizers. Meanwhile, Bottomley (1914aBottomley ( ,b, 1917Bottomley ( , 1920 asserted that small quantities of humic substances favored plant growth. However, Clark and Roller (1924) , although working closely with Bottomley, found that humic substances were not essential for plant growth.…”
Section: Historical Overviewmentioning
confidence: 99%
“…13 There are several isomeric forms, and assumedly the form found was 9,10-dihydroxyoctadecanoic acid, a compound produced by various soil fungi; this is the compound illustrated here. sick soil that led ultimately to the isolation and identification of dihydroxystearic Schreiner and his associates subsequently identified many more organic compounds in soils (Schreiner 1912, Shorey 1913, including terpenes, sterols (Schreiner and Shorey 1909a, 1909b, 1909c, hydrocarbons Shorey 1909a, 1911c), fatty acids Shorey 1910d, 1911c), phenolic acids and aldehydes 14 (Schreiner and Skinner 1914a, 1914b, 1914cShorey 1914;Skinner 1914Skinner , 1918aSkinner , 1918bSkinner , 1918cSkinner , 1918dSkinner and Noll 1916;Walters 1917) and nitrogenous compounds (Schreiner and Lathrop 1911c;Schreiner and Reed 1908b;Schreiner and Shorey 1907, 1910b, 1910cSchreiner and Skinner 1912a) (see Table 1). A useful summary of Schreiner's methods for extracting different groups of organic constituents from the soil was given by Thomas (1914).…”
Section: Soil Organic Compoundsmentioning
confidence: 99%